COVID-19 Advanced Care - Evangelia Fouka (MDPI AG, 2021)
The coronavirus disease 2019 (COVID-19) pandemic, related to the novel severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2), has caused a worldwide sudden and substantial burden in public health due to an enormous increase in hospitalizations for pneumonia with the multiorgan disease. Treatment for individuals with COVID-19 includes best practices for supportive management of acute hypoxic respiratory failure. Emerging data indicate that dexamethasone therapy reduces 28-day mortality in patients requiring supplemental oxygen compared with usual care, and ongoing trials are testing the efficacy of antiviral therapies, immune modulators and anticoagulants in the prevention of disease progression and complications, while monoclonal antibodies and hyperimmune globulin may provide additional preventive strategies. Consensus suggestions can standardize care, thereby improving outcomes and facilitating future research. This review discusses current evidence regarding the pharmacotherapy of COVID-19.